(Re)imagining "English Learners" as Transnational, Translingual, and Transracial English Speakers: Insights from a Single Subject Case Study at a Superdiverse Community College. - Jain, Rashi (Journal of Multilingual Theories & Practices, 2025)
As a vital subfield of English for specific purposes (ESP), there is a growing need for practitioners within English for academic purposes (EAP) settings to engage in Critical Language Awareness (Koester, 2022). Yet, EAP programs in the Global North often exist within monolingually and monoculturally oriented higher education contexts left largely untouched by the transformative discourses—including the more recent critical trans-turn as part of an emerging "trans-era" (Fang et al., 2022)—that have been gaining traction within academia (see Pontier & Tian, 2022). At the same time, higher education EAP classrooms in the United States are being rapidly changed by globalization and especially with the cross-migration of students and practitioners between the Global South and the Global North across a transnational English language teaching landscape (Jain et al., 2021, 2022), which is in turn contributing to a growing linguistic superdiversity (Zhang-Wu, 2022a) in those classrooms. As a community college–based pracademic endeavoring to "walk the talk, " I have been engaging in identity-as-pedagogy (Morgan, 2004), and draw upon my students' and my own transnational and translingual identities as part of my critical pedagogy (see Jain, 2021, 2022). Building upon my existing pracademic inquiries (see Jain, 2022), this integrated practitioner research (Jain, 2013) around a single subject case proposes that in such superdiverse settings, so-called "English learners (ELs)" can be (re)imagined from critical translingual, transnational, and transracial perspectives, especially when tensions emerge from teaching a target "standard" English variety while being responsive to the hybrid identities present in the classroom. Grounded in data generated organically across one semester of a capstone integrated skills course conducted via a continuing "structured remote teaching" format toward the end of a global pandemic (and interpreted through critical poststructural and postcolonial lenses), I examine how, as part of a Critical Language Awareness (CLA) approach, I incorporated elements of both critical pragmatism and progressivism (Pennycook, 1997; Ruecker & Shapiro, 2020; Shapiro, this issue) in my identity-as-pedagogy to decenter, decolonize, and deracialize academic English teaching and learning—with mixed results. I then offer a new framework to conceptualize ELs' intersectional identities, in response to the increasingly complex 21st century's global realities.